2008
DOI: 10.1101/gr.071548.107
|View full text |Cite
|
Sign up to set email alerts
|

No effect of recombination on the efficacy of natural selection in primates

Abstract: Population genetic theory suggests that natural selection should be less effective in regions of low recombination, potentially leading to differences in rates of adaptation among recombination environments. To date, this prediction has mainly been tested in Drosophila, with somewhat conflicting results. We investigated the association between human recombination rates and adaptation in primates, by considering rates of protein evolution (measured by d N /d S ) between human, chimpanzee, and rhesus macaque. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
52
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 77 publications
10
52
3
Order By: Relevance
“…Since b-values are typically between 0.1 and 0.3 in most species (Table S2), changes in N e tend to cause small changes in the proportion of effectively neutral mutations; for example, a 10-fold increase in effective population size will reduce the proportion of effectively neutral mutations by only 37% if b = 0.2. We find no evidence of a significant negative correlation between c and either u S or N e in humans, in agreement with the work of Bullaughey et al (2008). They found no evidence that the ratio of the nonsynonymous (d N ) to the synonymous (d S ) substitution rate between human, chimpanzee, and macaque was correlated to the rate of recombination.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…Since b-values are typically between 0.1 and 0.3 in most species (Table S2), changes in N e tend to cause small changes in the proportion of effectively neutral mutations; for example, a 10-fold increase in effective population size will reduce the proportion of effectively neutral mutations by only 37% if b = 0.2. We find no evidence of a significant negative correlation between c and either u S or N e in humans, in agreement with the work of Bullaughey et al (2008). They found no evidence that the ratio of the nonsynonymous (d N ) to the synonymous (d S ) substitution rate between human, chimpanzee, and macaque was correlated to the rate of recombination.…”
supporting
confidence: 81%
“…Furthermore, for our mouse species we are using an F 2 genetic linkage map constructed from intercrosses between M. m. domesticus and M. m. castaneus to infer recombination rates for M. m. castaneus. In humans it has previously been shown that diversity over divergence is correlated positively to recombination rate (Hellmann et al 2005) and that d n /d s is correlated to gene density (Bullaughey et al 2008). In contrast to Hellmann et al (2005), we do not find a significant correlation between N e and recombination rate, but they used long noncoding sequences to investigate diversity over divergence; their estimates were therefore subject to much less error than ours.…”
contrasting
confidence: 50%
See 1 more Smart Citation
“…It is, therefore, possible that a greater number of true PSGs exist in regions of high recombination for this reason. However, a recent study found no evidence that recombination affects the efficacy of selection in the human genome (Bullaughey et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Such differences may be related to the functional categories of genes that reside in regions of low recombination and/or to their expression level. Interestingly, in Drosophila, subsets of loci such as male-biased genes ( (Bullaughey et al 2008), but relationships between local recombination rates and DNA diversity in the human genome are weak (Hellmann et al 2005).…”
Section: Population Size and Rates Of Evolutionmentioning
confidence: 99%